Method for preparing high-performance resin catalytic material by using MOF (Metal Organic Framework) as template agent
By using MOF as a template agent, high-performance resin catalytic materials are prepared, which solves the problems of poor mass transfer performance and poor reuse performance of existing resins, and achieves high catalytic activity and stability, which are suitable for industrial catalytic reactions.
Patent Information
- Application Number
- CN202411795856.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
The existing commercial acidic ion exchange resins have poor mass transfer performance, insufficient catalytic activity, and poor reusability in catalytic systems, which limits its further development in industrial production.
Using metal organic frames (MOFs) as template agents, high-performance resin catalytic materials are prepared through suspension polymerization and sulfonic acid functionalization, and the pore structure of the resin is regulated to improve mass transfer performance.
A resin material with high catalytic activity and stability has been achieved, the transmission efficiency between reactants and products has been improved, the catalytic stability and reusable performance have been enhanced, and it is suitable for catalytic reactions such as esterification and transesterification.
Smart Images

Figure CN119708318A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic-inorganic composite material synthesis, and in particular relates to a method for preparing a resin catalytic material with high catalytic activity and high stability. Background Art
[0002] Acidic ion exchange resins play an important role in chemical production processes due to their advantages such as easy separation, high economic efficiency and good stability. However, commercial acidic ion exchange resins often have insufficient catalytic activity in the system due to poor mass transfer performance and inaccessible active sites, which limits their further development in industrial production.
[0003] Acidic ion exchange resins are usually polymerized with styrene as a monomer and divinylbenzene as a crosslinking agent, and then prepared by sulfonation with sulfuric acid. In order to improve the catalytic activity of acidic ion exchange resins, patent CN 1887424A discloses a cation exchange resin modified with tin dichloride, and uses it to catalyze the esterification reaction of ammonium lactate and alcohol to achieve a high yield of lactic acid esters; patent CN 116273177A discloses a new type of supported resin catalyst with palladium as an active component, and applies it to the reaction of methacrolein and methanol, and uses the active component palladium to achieve an increase in the conversion rate of methacrolein to more than 97%. However, this type of method of increasing the type and loading of active components and thus improving the activity of the resin by ion exchange, impregnation, etc. often has problems such as active component dropout and poor reusability.
[0004] In a catalytic system, the speed of reaction and mass transfer between reactants and products in the catalyst is an important factor affecting the yield of the product. By regulating the pore structure of the resin catalyst, its mass transfer performance can be improved, and then its catalytic performance can be improved. At present, toluene, n-heptane, polyethylene glycol, polyvinyl pyrrolidone, etc. are often added as porogens in the preparation process of the resin to obtain ion exchange resins that are beneficial to the transfer of reactants and products in the target system. However, the method of simply using porogens to regulate the pore structure of the resin has limitations such as excessive addition leading to sphere breakage and small controllable range of the pores, and the mass transfer performance of the resin cannot be further improved. Therefore, in order to give full play to the development of acidic ion exchange resins in the field of catalysis, it is necessary to develop a method for preparing high-performance resin catalytic materials. Summary of the invention
[0005] In order to overcome the problems of poor mass transfer performance and insufficient reusability of existing commercial resins, the present invention provides a method for preparing a resin catalytic material with high catalytic activity and high stability using MOF as a template.
[0006] To achieve the above object, the present invention adopts the following technical solution: A high-performance resin catalytic material is prepared using MOF as a template, and the preparation process includes the following steps: 1) Dissolve polyvinyl alcohol in water to generate an aqueous phase; 2) Ultrasonic mixing of monomers, crosslinking agents, porogens and initiators to generate an oil phase; 3) Adding MOF to the water phase or oil phase, and adding the oil phase to the water phase for suspension polymerization to obtain polymer microspheres encapsulating MOF; 4) The obtained polymer microspheres are washed and dried, stirred and dispersed in a solvent, and then concentrated sulfuric acid is added for sulfonic acid functionalization, and then washed and dried with deionized water and acetone to obtain the high-performance resin catalytic material.
[0007] Furthermore, the concentration of the polyvinyl alcohol aqueous solution obtained in step 1) is 0.2-1.2 g / L.
[0008] Furthermore, the monomer in step 2) includes one or more of styrene, ethylene, propylene, vinyl chloride, acrylonitrile, methyl methacrylate, ethyl acrylate, butyl acrylate, benzyl chloride, etc.; and the mass ratio of the polyvinyl alcohol used to the monomer is 0.3-1.5%.
[0009] Furthermore, the cross-linking agent in step 2) includes one or more of vinylbenzene, divinylbenzene, diisocyanate, N,N-methylenebisacrylamide, etc.; and its usage is 5-80% of the mass of the monomers used.
[0010] Furthermore, the porogen in step 2) includes one or more of n-heptane, toluene, ethylene dichloride, n-hexane, etc.; and the amount thereof is 20-130% of the mass of the monomers used.
[0011] Furthermore, the initiator in step 2) includes one or more of benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, cumene hydroperoxide, etc.; and the amount used is 1-5% of the mass of the monomer used.
[0012] Furthermore, in step 3), the MOF comprises one or more of UiO-66, ZIF-8, ZIF-11, etc. of different sizes; and the amount thereof is 0.05-10% of the mass of the monomers used.
[0013] Furthermore, in step 3), the solvent is 1,2-dichloroethane, toluene, etc.
[0014] Furthermore, the reaction temperature of the suspension polymerization in step 3) is 60-100°C, and the reaction time is 3-8 h.
[0015] Furthermore, the stirring time in step 4) is 0.5-1 h.
[0016] Furthermore, the amount of concentrated sulfuric acid in step 4) is converted to 10 mL per gram of polymer microspheres.
[0017] Furthermore, the reaction temperature of the sulfonic acid functionalization in step 4) is 65-80°C, and the reaction time is 1-5 h.
[0018] The beneficial effects of the present invention are: (1) Metal-organic framework (MOF) is a type of porous material with crystal sizes ranging from nanometers to micrometers. MOF has excellent hydrothermal stability and can be stably present in the water phase and oil phase of suspension polymerization. Therefore, it can be introduced as a template in the polymerization. At the same time, it is easily soluble in strong acids and can be easily removed during the sulfonation process, thereby realizing the design and optimization of the resin pore structure. Based on this, the present invention uses MOF as a template, and by regulating the type, size, and amount of MOF added, it can achieve the preparation of high-performance resin materials with a large range of hierarchical pore structures with an average pore size of 38 nm.
[0019] (2) The resin prepared by the method of the present invention not only maintains the advantages of mechanical stability and easy separation of the resin, but also has better mass transfer performance, which makes it more conducive to the transmission of reaction substrates and products and thus accelerates the conversion of reactants into products. Therefore, it can be used in catalytic reactions such as esterification and ester exchange, and has good reusability and universality. It is expected to become a type of macroporous acid catalyst in industrial processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The infrared spectra of the polymer white balls (a) encapsulated with MOF and the high-performance resin catalytic material (b) prepared in Examples 1, 2, 3 and 5.
[0021] Figure 2 This is the X-ray diffraction pattern of the polymer white ball encapsulated with MOF and the high-performance resin catalytic material prepared in Example 2.
[0022] Figure 3 N is the high performance resin catalytic material prepared in Examples 2 and 3. 2 Adsorption-desorption isotherms. DETAILED DESCRIPTION
[0023] The preparation of a high-performance resin catalyst material comprises the following steps: 1) Dissolve polyvinyl alcohol in water to generate an aqueous phase with a concentration of 0.2-1.2 g / L; 2) Ultrasonic mixing of monomers, crosslinking agents, porogens and initiators to generate an oil phase; 3) Add MOF to the water phase or oil phase, and add the oil phase to the water phase, and perform suspension polymerization at 60-100 °C for 3-8 h to obtain polymer microspheres wrapped with MOF; 4) The obtained polymer microspheres are washed and dried, dispersed in a solvent, stirred for 0.5-1 h, and then concentrated sulfuric acid is added, sulfonated at 65-80 °C for 1-5 h, and then washed and dried with deionized water and acetone to obtain the high-performance resin catalytic material.
[0024] The monomer includes one or more of styrene, ethylene, propylene, vinyl chloride, acrylonitrile, methyl methacrylate, ethyl acrylate, butyl acrylate, benzyl chloride, etc. The crosslinking agent includes one or more of vinylbenzene, divinylbenzene, diisocyanate, N,N-methylenebisacrylamide, etc. The porogen includes one or more of n-heptane, toluene, ethylene dichloride, n-hexane, etc. The initiator includes one or more of benzoyl peroxide (BPO), azobisisobutyronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, cumene hydroperoxide, etc. The MOF includes one or more of UiO-66, ZIF-8, ZIF-11, etc. of different sizes; the solvent is 1,2-dichloroethane, etc.
[0025] During the operation, the amount of polyvinyl alcohol used is 0.3-1.5% of the mass of the monomer; the amount of the cross-linking agent used is 5-80% of the mass of the monomer, the amount of the porogen used is 20-130% of the mass of the monomer, the amount of the initiator used is 1-5% of the mass of the monomer; the amount of the MOF used is 0.05-10% of the mass of the monomer; the amount of concentrated sulfuric acid used is converted to 10 mL per gram of polymer microspheres.
[0026] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0027] Example 1 (0.1) ZiF-D40H160-SO 3 Preparation of H Preparation of ZiF-8: Add 0.036 mol zinc nitrate hexahydrate (Zn(NO 3 ) 2 ⋅6H 2 O), stirred at room temperature for 24 h, the obtained white precipitate was centrifuged, washed with methanol 5 times, and then dried in an oven at 60 °C to obtain ZiF-8.
[0028] 0.1 g of polyvinyl alcohol was dissolved in 175 mL of water to generate an aqueous phase; styrene (15 g), divinylbenzene (8 g), n-heptane (18 g) and 0.5 g of BPO were mixed and dissolved by ultrasonication to generate an oil phase; 0.1 g of ZiF-8 was added to the oil phase and ultrasonicated for 30 min to make it uniformly dispersed in the oil phase, and then added to the aqueous phase, and suspended and polymerized at 85 °C and 180 rpm for 5 h to obtain polymer white balls (0.1) ZiF-D40H160 wrapped with ZiF-8, which were washed alternately with hot water and methanol to remove the unreacted organic phase, and then dried at 80 °C overnight; 1 g of the washed and dried white balls was dispersed in 12.5 g of 1, 2-dichloroethane, stirred at 60 °C for 30 min, and then 10 mL of concentrated sulfuric acid was added, and the temperature was raised to 85 °C to sulfonate 3 h later, it was washed and dried with deionized water and acetone to obtain a high-performance resin catalytic material (0.1) ZiF-D40H160-SO 3 H.
[0029] Example 2 (0.4) UiO-D40H160-SO 3 Preparation of H Preparation of UiO-66: 5 mmol ZrCl 4 and 5 mmol BDC were dissolved in a hydrothermal reactor containing 30 mL N,N-dimethylformamide and 11.7 mL formic acid, and reacted in an oven at 150 °C for 40 h. After cooling to room temperature, the obtained white solid was centrifuged and washed alternately with DMF and ethanol three times for 3 h each time, and dried in an oven at 80 °C to obtain UiO-66.
[0030] 0.1 g of polyvinyl alcohol was dissolved in 175 mL of water to generate an aqueous phase; styrene (15 g), divinylbenzene (8 g), n-heptane (18 g) and 0.5 g of BPO were mixed and dissolved by ultrasonication to generate an oil phase; 0.4 g of UiO-66 was added to the aqueous phase and stirred at 300 rpm for 30 min to make UiO-66 uniformly dispersed, and then the oil phase was added to the aqueous phase, and suspension polymerization was carried out at 85 °C and 200 rpm for 5 h to obtain polymer white balls (0.4)UiO-D40H160 wrapped with UiO-66, which were washed alternately with hot water and methanol to remove the unreacted organic phase, and then dried at 80 °C overnight; 1 g of the washed and dried white balls was dispersed in 12.5 g of 1,2-dichloroethane, stirred at 60 °C for 30 min, and then 10 mL of concentrated sulfuric acid was added, and the temperature was raised to 85 °C to sulfonate 3 h later, it was washed and dried with deionized water and acetone to obtain a high-performance resin catalytic material (0.4) UiO-D40H160-SO 3 H.
[0031] Example 3 (0.8) UiO-D40H160-SO 3 Preparation of H Preparation of UiO-66: 5 mmol ZrCl 4 and 5 mmol BDC were dissolved in a hydrothermal reactor containing 30 mL N, N-dimethylformamide and 11.7 mL formic acid, and reacted in an oven at 150 °C for 40 h. After cooling to room temperature, the obtained white solid was centrifuged and washed alternately with DMF and ethanol three times for 3 h each time, and dried in an oven at 80 °C to obtain UiO-66.
[0032] 0.1 g of polyvinyl alcohol was dissolved in 175 mL of water to generate an aqueous phase; styrene (15 g), divinylbenzene (8 g), n-heptane (18 g) and 0.5 g of BPO were mixed and dissolved by ultrasonication to generate an oil phase; 0.8 g of UiO-66 was added to the aqueous phase and stirred at 300 rpm for 30 min to make UiO-66 uniformly dispersed, and then the oil phase was added to the aqueous phase, and suspension polymerization was carried out at a temperature of 85 °C and a rotation speed of 220 rpm for 5 h to obtain a polymer white ball (0.8)UiO-D40H160 wrapped with UiO-66, which was washed alternately with hot water and methanol to remove the unreacted organic phase, and then dried at 80 °C overnight; 1 g of the washed and dried white ball was dispersed in 12.5 g of 1,2-dichloroethane, stirred at 60 °C for 30 min, and then 10 mL of concentrated sulfuric acid was added, and the temperature was raised to 85 °C to sulfonate 3 h later, it was washed and dried with deionized water and acetone to obtain a high-performance resin catalytic material (0.8) UiO-D40H160-SO 3 H.
[0033] Example 4 (0.4) UiO-D20H140-SO 3 Preparation of H Preparation of UiO-66: 5 mmol ZrCl 4 and 5 mmol BDC were dissolved in a hydrothermal reactor containing 30 mL N,N-dimethylformamide and 11.7 mL formic acid, and reacted in an oven at 150 °C for 40 h. After cooling to room temperature, the obtained white solid was centrifuged and washed alternately with DMF and ethanol three times for 3 h each time, and dried in an oven at 80 °C to obtain UiO-66.
[0034] 0.1 g of polyvinyl alcohol was dissolved in 175 mL of water to generate an aqueous phase; styrene (15 g), divinylbenzene (4 g), n-heptane (16 g) and 0.5 g of BPO were mixed and dissolved by ultrasonication to generate an oil phase; 0.4 g of UiO-66 was added to the aqueous phase and stirred at 300 rpm for 30 min to make UiO-66 uniformly dispersed, and then the oil phase was added to the aqueous phase, and suspension polymerization was carried out at 85 °C and 220 rpm for 5 h to obtain polymer white balls (0.4)UiO-D20H140 wrapped with UiO-66, which were washed alternately with hot water and methanol to remove the unreacted organic phase, and then dried at 80 °C overnight; 1 g of the washed and dried white balls was dispersed in 12.5 g of 1, 2-dichloroethane, stirred at 60 °C for 30 min, and then 10 mL of concentrated sulfuric acid was added, and the temperature was raised to 85 °C to sulfonate 3 h later, it was washed and dried with deionized water and acetone to obtain a high-performance resin catalytic material (0.4) UiO-D20H140-SO 3 H.
[0035] Example 5 (0.1) UiO-NDC (50%)-D40H160-SO 3 Preparation of H Preparation of UiO-66-NDC (50%): 0.5 g ZrCl 4 Dissolve in a polytetrafluoroethylene hydrothermal reactor filled with 50 mL of N,N-dimethylformamide, add 115 μL of deionized water. Then, add 1.6 mmol of terephthalic acid and 0.8 mmol of 1,4-naphthalenedicarboxylic acid (H 2 NDC) was added thereto, dissolved by ultrasonication, and reacted in a drying oven at 120 °C for 24 h. After cooling to room temperature, the obtained white solid was centrifuged and washed alternately with DMF and ethanol for three times, each time for 3 h, and dried in an oven at 80 °C to obtain UiO-66-NDC (50%).
[0036] 0.1 g of polyvinyl alcohol was dissolved in 175 mL of water to generate an aqueous phase; styrene (15 g), divinylbenzene (8 g), n-heptane (18 g) and 0.5 g of BPO were mixed and dissolved by ultrasonication to generate an oil phase; 0.1 g of UiO-66-NDC (50%) was added to the oil phase and continued to be dissolved by ultrasonication for 1 h, and then the oil phase was added to the aqueous phase. After suspension polymerization at 85 °C and 220 rpm for 5 h, a polymer white ball (0.1)UiO-NDC (50%)-D40H160 coated with UiO-66-NDC (50%) was obtained. The unreacted organic phase was removed by alternating washing with hot water and methanol, and then dried at 80 °C overnight; 1 g of the washed and dried white ball was dispersed in 12.5 g of 1,2-dichloroethane, stirred at 60 °C for 30 min, and then 10 mL of concentrated sulfuric acid was added, and the temperature was raised to 85 °C for sulfonation 3 h later, it was washed and dried with deionized water and acetone to obtain a high-performance resin catalytic material (0.1)UiO-NDC (50%)-D40H160-SO 3 H.
[0037] Figure 1 The infrared spectra of the polymer white balls (a) coated with MOF prepared in Examples 1, 2, 3, and 5 and the high-performance resin catalytic material (b) prepared after sulfonation are shown in the figure. -1 and 2922 cm -1 The characteristic absorption peak of the CH bond of the benzene ring is at 1601-1350 cm -1 The C=C stretching vibration peak of the benzene ring is at 700 cm -1 The absorption peak at 1034 cm is the bending vibration absorption peak outside the aromatic CH bond plane, which indicates the successful polymerization of polystyrene microspheres (a). After the polystyrene microspheres are sulfonated, they are affected by the symmetric stretching vibration of S=O, and the absorption peak at 1034 cm -1 and 1005 cm -1 At the same time, there is a doublet peak at 669 cm -1 A CS stretching vibration appears at the position of the polystyrene microspheres, indicating that the sulfonic acid group has been successfully attached to the polystyrene microspheres and the sulfonic acid resin has been successfully prepared (b).
[0038] Figure 2 The X-ray diffraction diagram of the polymer white ball wrapped with MOF prepared in Example 2 and the high-performance resin catalyst material obtained after sulfonation. Compared with the XRD diagram of (0.4) UiO-D40H160, it can be seen that the diffraction peak belonging to UiO-66 disappears after sulfonation, which indicates that the UiO-66 template is removed and the (0.4) UiO-D40H160-SO 3 H was successfully prepared.
[0039] Figure 3 N is the high performance resin catalytic material prepared in Examples 2 and 3. 2 - Adsorption-desorption curve. As can be seen from the figure, at a relative pressure of about 0.1, the adsorption amount is very small, indicating that it has almost no microporous structure, and as the relative pressure gradually increases, its isotherm morphology is similar to the type IV isotherm proposed by IUPAC, indicating that it has a mesoporous structure; at a relative pressure of 0.8-1.0, the desorption curves of different resin catalytic materials all show hysteresis loops to varying degrees, proving that their mesoporous volumes are different. This shows that the introduction of different amounts of UiO-66 can effectively regulate the pore structure of the resin.
[0040] Application Example 1 0.1352 g of (0.1) ZiF-D40H160-SO prepared in Example 1 was added 3 H catalytic material, n-butanol with an alcohol / acid molar ratio of 3 and levulinic acid were added to a round-bottom flask and magnetically stirred at 80 °C for 4 h. After the reaction, samples were taken for analysis. The experiment was repeated 3 times, and the unsulfonated (0.1) ZiF-D40H160 resin material was used as a comparison. The results showed that the use of (0.1) ZiF-D40H160-SO 3 The levulinic acid conversion rate of the H-catalyzed material was 38.6%, compared with only 8% using the (0.1)ZiF-D40H160 resin material.
[0041] Under the above reaction conditions, the prepared high-performance resin catalytic material (0.1) ZiF-D40H160-SO 3 The results of repeated use of H are shown in Table 1. As can be seen from Table 1, after repeated use for 10 times, the catalytic activity of the catalytic material is only slightly reduced, showing its excellent catalytic stability.
[0042] Table 1 (0.1) ZiF-D40H160-SO 3 Reusability of H in catalytic levulinic acid esterification
[0043] Application Example 2 0.1352 g of (0.4)UiO-D40H160-SO prepared in Example 2 was added 3 H catalytic material, n-butanol with an alcohol / acid molar ratio of 3 and levulinic acid were added to a round-bottom flask and magnetically stirred at 80 °C for 4 h. After the reaction, samples were taken for analysis. The experiment was repeated 3 times, and the (0.4)UiO-D40H160 resin material without sulfonation was used as a comparison. The results showed that the use of (0.4)UiO-D40H160-SO 3The levulinic acid conversion rate of the H-catalyzed material was 44.3%, compared with only 10% using the (0.4)UiO-D40H160 resin material.
[0044] Application Example 3 1.28 g of (0.4)UiO-D40H160-SO prepared in Example 2 was added 3 H catalytic material, ethanol with an alcohol / acid molar ratio of 5 and lactic acid were added to a round-bottom flask and magnetically stirred at 75 °C for 6 h. After the reaction, samples were taken for analysis. The experiment was repeated 3 times. The results showed that the use of (0.4)UiO-D40H160-SO 3 The lactic acid conversion rate of H catalytic material was 50.1%.
[0045] Under the above reaction conditions, the prepared high-performance resin catalytic material (0.4)UiO-D40H160-SO 3 The results of repeated use of H are shown in Table 2. As can be seen from Table 2, after repeated use for 10 times, the catalytic activity of the catalytic material is only slightly reduced, showing its excellent catalytic stability.
[0046] Table 2 (0.4)UiO-D40H160-SO 3 Reusability of H in catalytic lactic acid esterification reaction
[0047] Application Example 4 1.16 g (0.8) UiO-D40H160-SO prepared in Example 3 was added 3 H catalytic material, ethanol with an alcohol / acid molar ratio of 5 and lactic acid were added to a round-bottom flask and magnetically stirred at 75 °C for 6 h. After the reaction, samples were taken for analysis. The experiment was repeated 3 times. The results showed that the use of (0.8)UiO-D40H160-SO 3 The lactic acid conversion rate of H catalytic material was 70%.
[0048] Application Example 5 2.44 g of (0.1) UiO-NDC(50%)-D40H160-SO prepared in Example 5 was added 3 H catalytic material, methanol and sec-butyl acetate with an alcohol-ester molar ratio of 4 were added to a round-bottom flask and magnetically stirred at 60 °C for 3 h. After the reaction, samples were taken for analysis. The experiment was repeated 3 times. At the same time, the (0.1)UiO-NDC(50%)-D40H160 resin material without sulfonation was used as a comparison. The results showed that the use of (0.1)UiO-NDC(50%)-D40H160-SO 3The conversion of sec-butanol using the H-catalyzed material was 30%, compared to only 5% using the (0.1)UiO-NDC(50%)-D40H160 resin material.
[0049] Under the above reaction conditions, the prepared high-performance resin catalytic material (0.1) UiO-NDC (50%)-D40H160-SO 3 The results of repeated use of H are shown in Table 3. As can be seen from Table 3, after repeated use for 10 times, the catalytic activity of the catalytic material is only slightly reduced, showing its excellent catalytic stability.
[0050] Table 3 (0.1)UiO-NDC(50%)-D40H160-SO 3 Reusability of H in catalytic transesterification of sec-butyl alcohol
[0051] Application Example 6 0.1352 g of (0.8) UiO-D40H160-SO prepared in Example 3 was added 3 H catalytic material, n-butanol with an alcohol / acid molar ratio of 3 and levulinic acid were added to a round-bottom flask and magnetically stirred at 120 °C for 4 h. After the reaction, samples were taken for analysis. The experiment was repeated 3 times. The results showed that the use of (0.8)UiO-D40H160-SO 3 The yield of butyl levulinate for H catalytic material was 69.74%.
[0052] The above examples illustrate that the high-performance resin catalyst material prepared by the present invention is suitable for acid-catalyzed catalytic systems, especially esterification and transesterification systems.
[0053] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a high-performance resin catalytic material using MOF as a template, characterized in that: The following steps are involved: 1) Dissolve polyvinyl alcohol in water to generate an aqueous phase; 2) Ultrasonic mixing of monomers, crosslinking agents, porogens and initiators to generate an oil phase; 3) Adding MOF to the water phase or oil phase, and adding the oil phase to the water phase for suspension polymerization to obtain polymer microspheres encapsulating MOF; 4) The obtained polymer microspheres are washed and dried, stirred and dispersed in a solvent, and then concentrated sulfuric acid is added for sulfonic acid functionalization, and then washed and dried with deionized water and acetone to obtain the high-performance resin catalytic material.
2. The method according to claim 1, characterized in that The monomers include one or more of styrene, ethylene, propylene, vinyl chloride, acrylonitrile, methyl methacrylate, ethyl acrylate, butyl acrylate, and benzyl chloride.
3. The method according to claim 1, characterized in that The crosslinking agent includes one or more of vinylbenzene, divinylbenzene, diisocyanate, and N,N-methylenebisacrylamide.
4. The method according to claim 1, characterized in that: The porogen includes one or more of n-heptane, toluene, ethylene dichloride, n-hexane and the like.
5. The method according to claim 1, characterized in that The initiator includes one or more of benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and cumene hydroperoxide.
6. The method according to claim 1, characterized in that The MOF includes one or more of UiO-66, ZIF-8 and ZIF-11 of different sizes.
7. The method according to claim 1, characterized in that During the operation, the amount of polyvinyl alcohol used is 0.3-1.5% of the mass of the monomer; the amount of the cross-linking agent used is 5-80% of the mass of the monomer; the amount of the porogen used is 20-130% of the mass of the monomer; the amount of the initiator used is 1-5% of the mass of the monomer; the amount of the MOF used is 0.05-10% of the mass of the monomer; the amount of concentrated sulfuric acid used is converted to 10 mL per gram of polymer microspheres.
8. The method according to claim 1, characterized in that The reaction temperature of the suspension polymerization in step 3) is 60-100°C, and the reaction time is 3-8 h.
9. The method according to claim 1, characterized in that The stirring time in step 4) is 0.5-1 h; the reaction temperature of the sulfonic acid functionalization is 65-80 °C, and the reaction time is 1-5 h.
10. A high performance resin catalytic material prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation of macroporous strong-acid cation-exchange resin catalyst and use thereof in catalytic synthesis of methyl 2-keto-L-gulonate
CN101927185A
Preparation method of nano-pore resin solid acid for alkylation of butane and butylene
CN103611571A
Preparing method of nanopore fluororesin acid catalysts used for olefin hydration reaction
CN104001541A
Porous acidic resin catalyst, preparation method and applications thereof
CN105618137A
Polybenzimidazole film with nanometer porous structure and preparation method thereof
CN109233274A